MADḤ genre in Africa: an Incursion into Ibn nafi’s supplicatory panegyrics to his sufi mentor, Shaykh Salahudeen Pelewura (2018)
This article explores the place of madḥ amidst other traditional Arabic poetic themes in Africa with particular reference to Ibn Nafi‘ panegyric ode on his sūfi mentor. It analyses the salient poetic features of supplicatory panegyric in Nigeria and the extent of its patronage by Yoruba ‘Ulamā. The study proceeds to chronicle the genesis of the fraternity between the poet and his patron. Analysing the structural pattern adopted for the composition, the author discovers that the poem is triggered not only by spiritual impulse but also betrothal connection between the author and his patron.